Public debt sustainability in the Caribbean (ECLAC Port of SpainTT, 2008)
Analyzes public debt in the most indebted Caribbean - viz. Barbados, Belize, Guyana, Jamaica, Antigua and Barbuda, Dominica and St. Kitts and Nevis - from the standpoint of its sustainability.
Keywords: PUBLIC DEBT